The Solution to the Task of Analyzing the Reliability of Web Sites Using Python Parsing - Yevsieiev, V.; Uskov, S. (International Center of Scientific Research, 2024)
There are several important reasons for conducting a web page reliability analysis. First, the analysis allows you to make sure that the page is accessible to users, ensuring its incompleteness and efficiency. Second, it helps detect errors, such as code errors, structural issues, or server issues, that may occur and cause disruptions in page accessibility or functionality. In addition, performance analysis, including page load time, allows you to evaluate the efficiency and speed of the page, which is important for the user experience. Security analysis allows you to identify vulnerabilities, such as cross-site scripting or SQL injection vulnerabilities, that can cause security breaches and leak confidential information. Finally, monitoring the stability of the connection with the server helps to monitor the stability of the page and respond in time to possible problems with the infrastructure or network. All these aspects of website reliability analysis work together to ensure a high level of functionality, availability, performance and security for users.
Keywords: web page; Python Parsing; reliability analysis; Web Sites